Upside-Down but Headed in the Right Direction: Review of the Highly Versatile Cassiopea xamachana System - Ohdera, Aki H.; Abrams, Michael J.; Ames, Cheryl L.; Baker, David M.; Suescún-Bolívar, Luis P.; Collins, Allen G.; Freeman, Christopher J.; Gamero-Mora, Edgar; Goulet, Tamar L.; Hofmann, Dietrich K.; Jaimes-Becerra, Adrian; Long, Paul F.; et al. (Frontiers in Ecology and Evolution, 2018)
The upside-down jellyfish Cassiopea xamachana (Scyphozoa: Rhizostomeae) has been predominantly studied to understand its interaction with the endosymbiotic dinoflagellate algae Symbiodinium. As an easily culturable and tractable cnidarian model, it is an attractive alternative to stony corals to understanding the mechanisms driving establishment and maintenance of symbiosis. Cassiopea is also unique in requiring the symbiont in order to complete its transition to the adult stage, thereby providing an excellent model to understand symbiosis-driven development and evolution. Recently, the Cassiopea research system has gained interest beyond symbiosis in fields related to embryology, climate ecology, behavior, and more. With these developments, resources including genomes, transcriptomes, and laboratory protocols are steadily increasing. This review provides an overview of the broad range of interdisciplinary research that has utilized the Cassiopea model and highlights the advantages of using the model for future research. We dedicate this manuscript to Robert Trench, who inspired many of us to begin working in Cassiopea